Adolescent social media interaction and authorial stance in Indonesian teen fiction - Djenar, Dwi Noverini (UI Scholars Hub, 2014)
This article examines representations of adolescent social media interaction in two Indonesian teen novels to show how adolescent communication styles are typified. It is argued that public discourse on the potential danger of social media interaction is resounded in the novels. The article demonstrates that the authors of both novels take a similar moral stance on the issue of social media but use different rhetorical strategies for indexing that stance. Both draw on the social values of registers to communicate the stance. In Online addicted, standard Indonesian is used in narration to convey an authoritative voice and a stern moral tone, while the gaul register indexes an alignment with favourable aspects of the protagonist's character. In Jurnal Jo online, gaul is similarly given a positive value by virtue of its juxtaposition with the Alay register. In this novel, gaul is the preferred, standard register. In both novels, there is a strong orientation toward